O potencial dos sistemas agroflorestais na conexão do corredor ecológico sossego carantinga: uma abordagem socioambiental - Chaves, Juliana Costa (2021)
This research has as its theme the agroforestry systems as a modality of ecosystem restoration adopted by smallholder farmers and family farmers in the interior of Sossego Caratinga Ecological Corridor (CESC). This study aimed to understand, from a socio-environmental interpretation of the experience of the interviewed farms, what is the potential of agroforestry system to generate connection (connections) in this territory. For such, studies about Ecological Corridors, Territory, Family Farming, Forestry Restoration, and Agroforestry Systems were used as theoretical support. The methodology was based on a qualitative approach to a case study, with interviews with local farmers, guided by a semi-structured questionnaire. The study was conducted in Sossego-Caratinga Ecological Corridor, the first ecological corridor recognized by State Decree in Minas Gerais, and Rio Doce and Zona da Mata regions. This present study sought to understand the experience with agroforestry, the difficulties, the motivation, relationship with the environment, as well as the interaction of farmers with the CESC territory. Based on the interviews, it was possible to notice an engagement from the interviewees in the search for alternative production systems in which the environmental quality and the ecosystem restoration are present, as in the case of agroforestry systems, and agro-ecological systems practiced by some interviewees. The public authority attention in face of the motivation and inspiration of the farmers may result in public policies and conservancy projects, and more assertive restoration of ecosystems with the perspectives and expectations of the locals and, as a result, generate a higher adhesion. From the results of this study, it was not possible to state that the SAF's implantation favors the connection of native vegetation coverage, even having reached this purpose in the territorial landscapes of the interviewed properties. However, it could be concluded that the connection and the strengthening of social bonds within the territory may encourage the adoption of agroforestry systems as a possibility of restoration, in such model that incorporates a socio-productive dimension of income generation, healthy production and defense of work in the rural areas. It is possible to say that the potential connection that Ecological Corridors generates goes beyond the support of the gene flow of flora and fauna, also achieving the connection of the local social agents and strengthening their connection with the world.